Factors associated with computational thinking skills among colleges in the university - Tarigan, Wenny Pinta Litna; Paidi; Wiyarsi, Antuni; Handoyo, Luisa Diana; Nuryani, Hadistia Siti; Dewi, Rishe Purnama (Edelweiss Applied Science and Technology, 2024)
Computational Thinking (CT) skills are crucial for students in various academic disciplines. This study investigated the relationship between CT perspective, digital competence, and unplugged CT skills among college students. The study aimed to assess the influence of the CT perspective and digital competence onunplugged CT skills across different academic departments and programs. It also explored potential moderating effect of gender, grade level, study program, and GPA. The unplugged CT refers to practicing computational thinking skills without the use of Scratch applications. A cross-sectional survey design with a random sampling method was employed. Data was collected from 500 college students enrolled in bachelor’s degree programs (science and non-science) at seven universities in Indonesia, from December 2023 to April 2024. The CT skills was collected through 25-item-multiple-choice questions test. CT perspective and digital competence were measured using separate 15-item and 20-item questionnares, respectively, all administered on a 5-point Likert scale that was distributed via Google Form. A structural model with a partial least squares approach was used tp analyze the relationship between the variables. The results indicated that there was a positive relationship between CT perspectives, digital competence, and CT skills. There were significant differences in CT skills based on study program, grade, and GPAs, but not gender. Students in science programs, upper grades, and with higher GPAs demonstrated higher CT skills. This study highlights the importance of fostering CT perspective and digital competence to enhance unplugged CT skills in various academic contexts.